Talking to young children about war. (2nd June 2022) - Forster, Martin
Abstract : While media coverage has slowed since Russia's invasion of Ukraine, the indirect impact of this war will have far reaching consequences. The shocking scenes painted across news outlets and social media of human atrocities, hostages and burning buildings is enough to cause anxiety in a mature adult, let alone a child in their early years.